"These devices have not been made for older people's needs" – Older adults' perceptions of digital technologies in Finland and Ireland. (August 2020) - Pirhonen, Jari; Lolich, Luciana; Tuominen, Katariina; Jolanki, Outi; Timonen, Virpi
Abstract: This article examines how older adults use and perceive digital technologies in Finland and Ireland. These two countries are at different stages regarding two important global trends – demographic ageing and digitalization. Finland, being the fastest ageing society in Europe, is also one of the leaders in implementing digital technologies in social and health care services. In contrast, Ireland is a demographically younger and less digitalized society. Drawing on focus group discussions on the usage of digital technologies, conducted with older adults in both countries, we analyse how digital technologies are adopted and viewed by older generations. The analyses showed that older adults associate digitalization with both advantages and drawbacks. To encapsulate these two contrasting aspects, we developed the term Janus-faced conceptions of technology. This concept encapsulates how the successful adoption of digital technology facilitates everyday activities whereas the inability to utilise technologies results in feelings of alienation and being out-of-touch. The digital divide was found to occur not only between generations but also between different socioeconomic groups of older adults. Highlights: Older adults need training, support, and easy access helplines to use technologies. Digitalization may increase inequality between generations and among older adults. Digitalization of services may increase inequality in access to public services. The advantages and drawbacks of digitalization need to be acknowledged. Digital technology may exacerbate feelings of being old and alienated from society.